Cloning Nacre's 3D Interlocking Skeleton in Engineering Composites to Achieve Exceptional Mechanical Properties. Issue 25 (2nd May 2016) - Zhao, Hewei; Yue, Yonghai; Guo, Lin; Wu, Juntao; Zhang, Youwei; Li, Xiaodong; Mao, Shengcheng; Han, Xiaodong
Abstract : Ceramic/polymer composite equipped with 3D interlocking skeleton (3D IL) is developed through a simple freeze‐casting method, exhibiting exceptionally light weight, high strength, toughness, and shock resistance. Long‐range crack energy dissipation enabled by 3D interlocking structure is considered as the primary reinforcing mechanism for such superior properties. The smart composite design strategy should hold a place in developing future structural engineering materials.